Storytelling Method using Finger Pool to Improve the Expressive Language Ability of Moderately Independent Students Class II SDN Raharja Tanjungsari - Farhan, Mochamad; Rochyadi, Endang; Tarsidi, Iding; Novianti, Ranti (Angstrom Centre of Education, 2023)
The purpose of this research is to improve the expressive language skills of mentally retarded students in class II SLB Raharja Mandiri using the storytelling method through finger puppet media. This study uses the Mix Methods Research method, which is a combination of qualitative and quantitative methods. The research design carried out in this study was the Exploratory Mixed Methods Research Design, which is a combination research method that combines qualitative and quantitative methods. The experimental method used in this research is Single Subject Research (SSR). Meanwhile, the type of experimental design that will be used in this second stage is the multiple baseline cross-subject type. The use of telling stories using finger puppets is believed to be able to improve expressive language skills with moderate mental retardation.